Pengelolaan Sumberdaya Lingkungan Pesisir Menggunakan Foto Udara di Tanjung Riau, Kota Batam - Roziqin, Arif; Gustin, Oktavianto; Pratama, Rizki Widi; Saragih, Fratia Yunirahma; Putri, Renita Adetia; Maharani, Firda Muthia; Sinaga, Kristina Miranda (Seminar Nasional Lahan Suboptimal, 2023)
Roziqin, A., Gustin, O., Pratama, R.W., Saragih, F.Y., Putri, R.A., Maharani, F.M., Sinaga, K.M. (2023). Management of coastal environmental resources using aerial photo in Tanjung Riau, Batam City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 607-615).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The coast is a land area that is still influenced by marine activities. The coastline is the boundary between land and sea areas, which influences the dynamics of coastal areas. Coastal areas are basically rich in natural resources, have many attractions, so they need to be managed by both the local community and the government to improve the local economy. The aimed of this research is to identify problems and potential coastal environmental resources. The study location is on the coast of Tanjung Riau, Batam City which has coastal resource potential that can be managed and developed to meet the needs of the surrounding community. The method used is observation and utilization of aerial photo data on parts of the Tanjung Riau coast which are then mapped and analyzed further to manage coastal environmental resources. The results obtained show that the Tanjung Riau coastal area has several problems such as waste, damaged ecosystems and organisms, while coastal potential includes fisheries, availability of piers and beach tourism.